Isolation and identification of blueberry postharvest decay pathogen and control effect of 2,4-epibrassinolide - Jia, Shaofeng; Hou, Zihuan; Li, Ke; Lu, Chunze; Ma, Jing; Wu, Lin; Li, Jinying; Li, Yanan; Wang, Ying (Frontiers in Plant Science, 2026)
Due to its thin, juicy skin and high physiological activity, blueberries are easily susceptible to damage by pathogenic bacteria during storage and transportation after harvest. However, there are relatively few studies on the mechanisms by which blueberries resist rot disease. Therefore, in this study, the blueberry cultivar ‘Northland’ was used as the experimental material. Using a combination of single spore isolation, morphological analysis, and molecular biology methods, the types of pathogenic bacteria responsible for postharvest decay of blueberries were investigated, as well as the mechanisms by which EBR influences disease resistance and quality control. The results indicated that the pathogen responsible for blueberry fruit rot was Talaromyces amestolkiae, and treatment with 2,4-epibrassinolide (EBR) could significantly reduce both the fruit rot rate and the disease index. Among the treatments, 0.4 mg/L EBR showed the most pronounced effect, effectively maintaining fruit firmness, titratable acidity, and soluble solids content, while reducing weight loss, decreasing the extent of membrane lipid peroxidation, and enhancing the activities of antioxidant enzymes such as superoxide dismutase (SOD) and peroxidase (POD) by 251.46% and 208.18%, respectively. Additionally, the activity of pathogenesis-related proteins, including chitinase, increased, and the stability of antioxidants, such as total phenols, was preserved. EBR improved the disease resistance of blueberry fruit through multi-pathway synergy and delayed the deterioration of postharvest quality. The findings of this study can offer theoretical support for the eco-friendly prevention and management of postharvest diseases in blueberries.